Impact Self-Efficacy and Supervisor Support on Transfer of Training: Two-Stage Approach Analysis - Iswahyudi Iswahyudi; Corry Yohana; Mardi Mardi (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
The training program has the ultimate goal and the knowledge gained in the training can be transferred back to work. This study aims to determine the effect of Self-Efficacy and Supervisor support on Transfer Training through Motivation to Transfer. The sample in this research is the PMQ employee at PT. Sumatra Prima Fibreboard. The sample technique used was purposive sampling, namely employees who had participated in the PMQ Skills training program with a valid total response of 203 respondents. Data collection was done by collecting questionnaires using the 5 Likert point scale. The data analysis method used in this study was Partial Least Squares-Structural Equation Modeling (PLS-SEM) using WarpPLS version 5. The results showed that Self-Efficacy, Supervisor Support, and Motivation to Transfer from a positive and significant provider for Transfers of Training. Self-Efficacy and Supervisor Support are positive and significant variables in influencing Motivation to Transfer. The results of the study also showed that Self-Efficacy and Supervisor support had a significant and significant effect on Transfer Training through Motivation to Transfer.